MÖCKEL, C. Philosophie des 20. Jahrhunderts - Wegmarken: Ausgewählte Schriften (1976-2021) mit einer autobiographischen Einführung. Logos: Berlim, 2022, 554 pp. - Garcia, Rafael Rodrigues (Studia Kantiana, 2023)
sem resumo